2023
DOI: 10.3390/s23020598
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Design Characteristics of Woven Textile Electrodes for long−Term ECG Monitoring

Abstract: An electrocardiograph records the periodic voltage generated by the heart over time. There is growing demand to continuously monitor the ECG for proactive health care and human performance optimization. To meet this demand, new conductive textile electrodes are being developed which offer an attractive alternative to adhesive gel electrodes but they come with their own challenges. The key challenge with textile electrodes is that the relationship between the manufacturing parameters and the ECG measurement is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…It was found that the more space there was, the more noise there was as well as larger signal amplitude waveforms. Although resistance varies depending on the type of conductive yarn, there was little variation in capacitance with the type of yarn [132]. Most of the previous studies have shown that the larger the electrode is in diameter, the better the signal quality and the lower the skin contact impedance [133].…”
Section: Electrode Designmentioning
confidence: 97%
“…It was found that the more space there was, the more noise there was as well as larger signal amplitude waveforms. Although resistance varies depending on the type of conductive yarn, there was little variation in capacitance with the type of yarn [132]. Most of the previous studies have shown that the larger the electrode is in diameter, the better the signal quality and the lower the skin contact impedance [133].…”
Section: Electrode Designmentioning
confidence: 97%
“…The electrodes form an integral part of the textile, which is then made into a wearable item that provides tight contact between the electrodes and the skin to reduce signal noise generated via the movement of the electrodes. Electrodes are mainly made by depositing conductive inks/paste on textiles using printing [155][156][157], coating the textile in the electrode material solution [158,159] or knitting [160,161], weaving [162,163], or embroidering [164,165] commercially available…”
Section: Electrodes For Heart Rate Heart Rate Variability and Muscle ...mentioning
confidence: 99%
“…The electrodes form an integral part of the textile, which is then made into a wearable item that provides tight contact between the electrodes and the skin to reduce signal noise generated via the movement of the electrodes. Electrodes are mainly made by depositing conductive inks/paste on textiles using printing [155][156][157], coating the textile in the electrode material solution [158,159] or knitting [160,161], weaving [162,163], or embroidering [164,165] commercially available conductive yarns or bespoke conductive yarns such as graphene-based yarn and PDOT: PSS-modified yarn [166,167] EMG is used to monitor muscle excitation using the biological electrical activity signals of the muscle, which can provide useful indicators of muscle activation patterns, fatigue, and performance. EMG has an important role in analysing dynamic movement and understanding the role of a muscle in a specific movement [171].…”
Section: Electrodes For Heart Rate Heart Rate Variability and Muscle ...mentioning
confidence: 99%
“…Some cordless devices for ECG recordings and wireless data transmission via Bluetooth and Wi-Fi report only about heart rate, not ECG recordings and none of them provide signal quality assurance data that are directly compared with Holter monitoring [5][6][7][8]. Design of textile -based multichannel ECG systems that measure ECG signals from several parts of patients' torso were described in papers [9][10][11][12][13]. Smart or electronic textile (e-textiles) is a material that can interact with environment and users.…”
Section: Introductionmentioning
confidence: 99%